Contactless conductivity detection for analytical techniques: Developments from 2010 to 2012. Issue 1 (3rd December 2012) - Kubáň, Pavel; Hauser, Peter C.; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> The developments in the field of capacitively coupled contactless conductivity detection in the approximate period from July 2010 to June 2012 are traced. Few reports concerning fundamental studies or new detector designs have appeared. On the other hand, applications in standard CZE are flourishing and contactless conductivity measurements are increasingly being employed as part of novel or more sophisticated experimental systems. Work on the lab‐on‐chip devices integrating contactless conductivity detection is continuing. A range of reports on the use of the simple yet powerful detection technique of contactless conductivity measurements in chromatographic separation as well as for analytical methods not including a separation step have also appeared.